2022
DOI: 10.3389/fphar.2022.911663
|View full text |Cite
|
Sign up to set email alerts
|

Trametes robiniophila Murr Sensitizes Gastric Cancer Cells to 5-Fluorouracil by Modulating Tumor Microenvironment

Abstract: Trametes robiniophila Murr (TRM) is a traditional Chinese medicine which has been used in clinics for enhancing immunity and improving the efficacy of chemotherapy. However, the mechanisms of action of TRM are unknown. In the previous study, we found that the Trametes robiniophila Murr n-butanol extract (TRMBE) comprises the major bioactive components of TRM. In the present study, we aimed to assess the combinational effects of TRMBE and 5-fluorouracil (5-FU) on the treatment of gastric cancer (GC) and explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…It is worth noting that the 5-FU (10 mg/kg) group as a positive control did not inhibit tumor growth from MFC sources. Referring to two studies using MFC for tumor formation and both treated with a dose of 5-FU (10 mg/kg), the first study used 5-FU (10 mg/kg, once a day), which significantly decreased tumor size compared to that in the control group 44 , while the second study used 5-FU (10 mg/kg, once every two days), which did not significantly change tumor size compared to that in the control group 45 . A comparison of the two studies revealed that the failure to inhibit tumor growth may be related to the frequency of drug injection, as our study used 5-FU (10 mg/kg, once every two days).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the 5-FU (10 mg/kg) group as a positive control did not inhibit tumor growth from MFC sources. Referring to two studies using MFC for tumor formation and both treated with a dose of 5-FU (10 mg/kg), the first study used 5-FU (10 mg/kg, once a day), which significantly decreased tumor size compared to that in the control group 44 , while the second study used 5-FU (10 mg/kg, once every two days), which did not significantly change tumor size compared to that in the control group 45 . A comparison of the two studies revealed that the failure to inhibit tumor growth may be related to the frequency of drug injection, as our study used 5-FU (10 mg/kg, once every two days).…”
Section: Discussionmentioning
confidence: 99%
“…The cell cycle and apoptosis assays were performed as described previously ( Li et al, 2022 ; Xu et al, 2022 ). Briefly, the PD-treated cells were harvested, washed, and fixed.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were monitored for body weight and tumor size (length × width 2 × 0.5) once a week according to the animal protocol. After 4 weeks, the nude mice were sacrificed, and the tissues were collected for detection [ 40 ]. The number of macroscopic nodules was then recorded.…”
Section: Methodsmentioning
confidence: 99%